Assessment of a Functional Electromagnetic Compatibility Analysis of Near-Body Medical Devices Subject to Electromagnetic Field Perturbation - Razek, Adel (Electronics (Basel), 2023)
This article aims to assess, discuss and analyze the disturbances caused by electromagnetic field (EMF) noise of medical devices used near living tissues, as well as the corresponding functional control via the electromagnetic compatibility (EMC) of these devices. These are minimally invasive and non-ionizing devices allowing various healthcare actions involving monitoring, assistance, diagnoses and image-guided medical interventions. Following an introduction of the main items of the paper, the different imaging methodologies are conferred, accounting for their nature, functioning, employment condition and patient comfort and safety. Then the magnetic resonance imaging (MRI) components and their fields, the consequential MRI-compatibility concept and possible image artifacts are detailed and analyzed. Next, the MRI-assisted robotic treatments, the possible robotic external matter introductions in the MRI scaffold, the features of MRI-compatible materials and the conformity control of such compatibility are analyzed and conferred. Afterward, the embedded, wearable and detachable medical devices, their EMF perturbation control and their necessary protection via shielding technologies are presented and analyzed. Then, the EMC control procedure, the EMF governing equations and the body numerical virtual models are conferred and reviewed. A qualitative methodology, case study and simple example illustrating the mentioned methodology are presented. The last section of the paper discusses potential details and expansions of the different notions conferred in the paper, in the perspective of monitoring the disturbances due to EMF noise of medical devices working near living tissues. This contribution highlights the possibility of the proper functioning of medical instruments working close to the patient’s body tissues and their protection by monitoring possible disturbances. Thanks to these commitments, various health recommendations have been taken into account. This concerns piezoelectric actuated robotics, assisted with MRI and the possible use of conductive materials in this imager under certain conditions. The safe use of onboard devices with EMF-insensitive or intelligently shielded materials with short exposure intervals is also of concern. Additionally, the need to monitor body temperature in case of prolonged exposure of onboard devices to EMF is analyzed in the Discussion section. Moreover, the use of virtual tissue models in EMC testing to achieve more realistic evaluation capabilities also features in the Discussion section.